New international legal order : in commemoration of the tenth anniversary of the Xiamen Academy of International Law - Cheng, Jiarui; Xiamen Academy of International Law (Leiden ; Boston : Brill, 2017)
A new international legal order (NILO) has progressively infiltrated the traditional scope of international law. Lectures delivered in the last ten years of the Xiamen Academy of International Law's summer programmes have recorded the emergence of this NILO. The essays contained in this book display a remarkable intellectual vitality and illustrate the new initiatives contributing to an NILO in the realm of international law. In addition to new concepts of the use of force, boundary disputes and self-determination, and new judicial practices in environmental law, these essays demonstrate a convergence towards a universal value of a globalised world, centred upon human security and reflected in international economic, technological, social and humanitarian cooperation -- sources of new tranches of international law. The contributors to this book have provided an in-depth analysis of such cooperation between various branches of international law.
Introduction / Chia-Jui Cheng -- Historical record of the Xiamen Academy of International Law / Chia-Jui Cheng -- Xiamen Academy of International Law and the future of the global legal order / Hisashi Owada -- Three concepts of UN reform / Danilo Turk -- Use of force : the general prohibition and its exceptions in modern international law and practice / Stephen Mathias -- Self-determination, Uti Possidetis and boundary disputes in Africa / Malcolm N. Shaw -- International judiciary practice in the development of international environmental law : a decade review / Xue Hanqin and Solene Guggisberg -- International organizations and the rule of law : challenges ahead / Jose Enrique Alvarez -- Asian and Pacific international organizations : mainstream or Sui Generis? an international institutional law perspective / Niels Blokker -- Methodological problems in international economic law and adjudication / Ernst-Ulrich Petersmann -- Belt and road initiative in the context of globalization / Guiguo Wang -- Technological development as a challenge for the development of air and space law / Stephan Hobe -- International humanitarian law in context / Christopher Greenwood.
Includes bibliographical references and index.
Keywords: Xiamen Academy of International Law; Xiamen Academy of International Law; International law; International law